A World Made for Money : Economy, Geography, and the Way We Live Today - Wallach, Bret, 1943- (Book collections on Project MUSE., 2015)
"A spirited and incisive survey of economic geography, A World Made for Money begins with the author stopped at a red light in Norman, Oklahoma. Observing the landscape of drugstores and banks, and for that matter the stoplight and roads themselves, Bret Wallach observes, 'Everything I see has been built to make money' or, at the very least, to facilitate making money. This, he argues, is a global phenomenon that nonetheless has occurred only within the past hundred years or so. Although guidebooks and culture brokers often disparage these landscapes of commerce, Wallach--recipient of a MacArthur 'genius grant'--argues that we would do well to pay them close attention. A World Made for Money provides a compelling, condensed tour of our world. From Silicon Valley to Sri Lanka, from post-Soviet Russia to post-apartheid South Africa, Wallach looks at how human beings are buying, manufacturing, working, growing and shipping food, and accessing the natural resources to fuel it all. These essential facets of daily life, propelled by the profit motive, represent a transnational force shaping our surroundings and environment in ways that may not always be beautiful (or even healthy) but that are fundamental to understanding how the world works in the twenty-first century. Wallach examines the relationship between acquisitiveness and landscape, reveals surprising contradictions and nuances, and provides fresh perspective on politically charged topics such as sprawl, deindustrialization, and agribusiness."--